2015
DOI: 10.1093/heapro/dav057
|View full text |Cite
|
Sign up to set email alerts
|

It is pleasant and heavy: convergence of visual contents in tobacco, alcohol and food marketing in Brazil

Abstract: The tactical use of visuoperceptual content in marketing may encourage impulsive consumption of unhealthy products. In this study, the application of visuoperceptual content was compared in advertisements used by industries of tobacco, alcohol and food. The aim was to ascertain whether similarities exist in the strategies used as variables for the selection of commercial stimuli, such as color, position and size. Scion Image and Corel Draw Graphics Suite software were used to analyze the content of a non-proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
(86 reference statements)
0
6
0
1
Order By: Relevance
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
“…The main findings of this review can be described as follows: a) most foods and beverages advertised in television are ultra-processed foods and have low nutritional value 24,27,29,31,34,[36][37][38]40,43,49,52,53,56,57,59 ; b) children's television programming contains several food advertisements and many studies found advertisements for this demographic group had a lower nutritional value compared with general audience programming 24,28,40,43,52,56,57 ; c) food packages can be deceiving especially to children who have a literal interpretation of what is printed on the packaging 35,50,58 ; d) proximity to unhealthy foods may increase the consumption of these foods 25,26,30,32,34,38,42,44,46,54 . These findings enhance the necessity of implementing statutory policies covering all marketing channels and robust nutritional standards as the case of the Chilean regulations approved in 2012 60 .…”
Section: Other Marketing Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…O "Galpão decorado" deixa a edificação livre para realizar outros argumentos retóricos que podem partir de outras espécies de argumentos técnicos ou até não técnicos. No caso do McDonald's, vemos o uso do vermelho na edificação, buscando criar emoções (páthos) de expansividade, alerta, força e excitação no receptor da mensagem (Viacava et al, 2016). iv Os autores defendem o uso do "Galpão decorado" "com uma frente retórica e fundos convencionais" (Venturi et al, 2003, p. 119) em detrimento do "Pato", que seria mais custoso em termos monetários, não teria a livre capacidade de resolver funcionalmente o restante do programa de necessidades e levaria a um ato retórico unidimensional.…”
Section: Estratégias De Retórica E Mimese Nos Modelos De Aprendendo Cunclassified